2002
DOI: 10.1002/cne.10212
|View full text |Cite
|
Sign up to set email alerts
|

Developmental timing of hair follicle and dorsal skin innervation in mice

Abstract: The innervation of hair follicles offers an intriguing, yet hardly studied model for the dissection of the stepwise innervation during cutaneous morphogenesis. We have used immunofluorescence and a panel of neuronal markers to characterize the developmental choreography of C57BL/6 mouse backskin innervation. The development of murine skin innervation occurs in successive waves. The first cutaneous nerve fibers appeared before any morphological evidence of hair follicle development at embryonic day 15 (E15). St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 77 publications
(167 reference statements)
6
71
0
Order By: Relevance
“…Our time course data confirm previous analyses for these structures (2,10,11,13,21,28), which demonstrated that follicles, sensory afferents, and Merkel cell clusters develop prenatally, whereas APMs and sebaceous glands develop postnatally (Fig. 7).…”
Section: Developmental Time Course and Patterns Of Fz6 Expression In supporting
confidence: 90%
See 2 more Smart Citations
“…Our time course data confirm previous analyses for these structures (2,10,11,13,21,28), which demonstrated that follicles, sensory afferents, and Merkel cell clusters develop prenatally, whereas APMs and sebaceous glands develop postnatally (Fig. 7).…”
Section: Developmental Time Course and Patterns Of Fz6 Expression In supporting
confidence: 90%
“…If, as suggested by Nurse and Diamond (3), the semicircular arrangement of Merkel cells is important for Follicle-Associated Nerve Endings. Any assessment of the geometry of hair follicle innervation faces the challenge that each follicle is innervated by multiple cutaneous sensory afferents, thus precluding the use of neurofilament immunostaining or other nonselective methods for visualizing the structure of individual afferents (11). Recently, Badea et al (26) described a genetically directed approach for sparse histochemical labeling of individual cutaneous afferents using tamoxifen-controlled neuron-specific Cre recombination to activate the expression of a membraneanchored alkaline phosphatase (AP) reporter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue samples of DBA/2J-or BALB/c-mated CBA/J female mice were perfusion-fixed using a mixture of paraformaldehyde and picric acid (Peters et al 2002). The density of TAC C and CALCA nerve fibres was determined in 14 mm-thick sections.…”
Section: Sp and Cgrp Stainingmentioning
confidence: 99%
“…These cells generate diverse peripheral nervous system derivatives, including the peripheral nerves that eventually innervate targets that include the skin. Interestingly, multipotent NC stem cells (NCSCs) are present in the rodent peripheral sciatic nerve at E15 (Morrison et al 1999), the time-point when (i) mouse back skin is first innervated (Peters et al 2002), (ii) SKPs are first detected in mouse back skin (Fernandes et al 2004), and (iii) the follicle dermal papillae first form from a population of cells expressing TrkC and p75NTR (Botchkarev et al 1998(Botchkarev et al , 1999, both of which are expressed on NC precursors (Stemple & Anderson 1992;Luo et al 2003). Within the peripheral nerve, these NCSCs then apparently disappear by birth (Morrison et al 1999), something that has been attributed to their terminal differentiation within the nerve itself.…”
Section: Implications and Unresolved Questions (A)mentioning
confidence: 99%